The impact of general education in enhancing the self-efficacy of accounting students at universities of technology - Naidoo, S. K.; Govender, S. (South African Journal of Higher Education, 2021)
The aim of this article is to investigate the integration of General Education in improving the Self-efficacy of Cost and Management Accounting (CMA) students to assess whether Self-efficacy, is having any positive impact on the students’ academic performance. The research design of this article was descriptive, longitudinal and employed a mixed-method approach. The nature of the quasi-experimental approach that was used in the current article is a non-equivalent pre-test and post-test control group design. The target population was CMA students. A census survey was performed. Findings, which were analysed with the aid of descriptive statistics, indicate a significant correlation in the post-test (Self-efficacy) scores of the group that undertook the General Education Modules and not the group that did not undertake the General Education Modules. This article recommends the implementation of General Education skills into the curriculum and a General Education intervention strategy. Moreover, these skills appear to be very poor amongst current learners and respondents believed that Self-efficacy could have a positive effect on the academic performance of learners.